Impact of Eisenia fetida populations on bioâconversion of paper mill solid wastes - Devjani Mohapatra; K. Sahoo; A. K. Sannigrahi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Huge quantity of paper mill wastes are dumped at the outskirt of factory as unwanted materials. Vermicomposting is an eco-friendly technique for beneficial conversion of different biodegradable/organic wastes into useful organic manure utilizing earthworms. Solid wastes generated in paper mills contain appreciable quantity of organic matter. Attempt was made for bio-conversion of Emami paper mill wastes with different numbers of Eisenia fetida (5â30 earthworms/2 kg substrate) for studying its influence on vermi-conversing time and quality of prepared vermicompost. Method Vermicomposting was carried out in trays following heap method and quality of final product was determined following both chemical analysis and bioassay on wheat seedlings. Results Application of more earthworms up to 20 numbers per 2 kg substrate made bio-conversion quicker but further addition of earthworm, however, delayed the process as some earthworms came out of beds and died probably due to competition for food among earthworms inside beds. Ten earthworms per kg paper mill wastesâsaw dustâcow dung mixture (1:0.5:0.5 weight wise) was found as optimum earthworm population for preparing quality vermicompost having more major and secondary plant nutrients. Bioassay of this manure on wheat seedlings also confirmed the analytical findings. Conclusion It is confirmed that earthworm population in vermibed played vital role in faster decomposition of paper mill wastes and releasing of more nutrients, which ultimately helped in better growth of wheat seedlings. Successful demonstration of vermicomposting technique will encourage local farmers for beneficial utilization of paper mill wastes in their agriculture.